Dipole models of proper ferroelectrics NaNO₂ and Sn(Pb)₂P₂S(Se)₆ - Drobnich, A.; Vysochanskii, Yu. (Condensed Matter Physics, 1998)
На прикладi кристалу NaNO₂ аналiзуються ізінгівські дипольні моделi сегнетоелектричних кристалів з введенням локального поля макровзiрця i без нього. Нами розроблена iзінгiвська дипольна
модель сегнетоелектрикiв сiм’ї Sn₂P₂S(Se)₆ . Розрахунки методом Монте-Карло показали, що при виборi певного коефiцiєнта короткодiї можна отримати такі температурнi границi фаз для
“опорних” кристалiв цiєї сiм’ї: Sn₂P₂S₆ – T ∗0 ∼ 10.5; Sn₂P₂Se₆ – T ∗ c ∼ 8.5, T ∗ i ∼ 9.5 (в приведених температурах), що кiлькiсно узгоджується з даними експерименту. Точка Лiфшиця з координатою x ∼ 0.27 спостерiгається на концентрацiйних дiаграмах в моделi
змiшаного кристалу Sn₂P₂ (SₓSe₁₋ₓ)₆ , що узгоджується з реальними даними. Для змiшаних кристалiв типу (Pb y Sn₁₋y )₂P₂S₆ i (Pb y Sn₁₋y)₂P₂Se₆ атоми Pb вiдiграють роль домiшок з нульовим дипольним моментом. Для цих кристалiв застосовується розбавлена iзінгiвська модель. We consider a NaNO₂ crystal as to the peculiarities of Ising dipole models of ferroelectic crystals. The models with the local field of a macroscopic sample and without this field were considered. A dipole Ising model of Sn₂P₂S(Se)₆ ferroelectics has been developed. As a result of the calculations done by the Monte-Carlo method it has been found that when a certain short-range interaction coefficient in Sn₂P₂S₆ is selected, the intermediate modulated phase disappears in a model with the local field. In this case the temperatures of phase transitions (PT) are as follows: for the Sn₂P₂S₆ model T * 0 ∼ 10.5; for the Sn₂P₂Se₆ model T ∗ c ∼ 8.5, T∗ i ∼ 9.5 (in effective temperatures). These data are in satisfactory agreement with the results of the real experiment. The concentration dependences of temperatures of PT in Sn₂P₂ (SₓSe₁₋ₓ)₆ crystals are simulated and the Lifshitz point is observed. In mixed (Pb y Sn₁₋y )₂P₂S₆ and (Pb y Sn₁₋y)₂P₂Se₆ crystals the increase of Pb concentration causes
reduction of temperatures of PT to 0 K. In this case the character of PT remains unchanged. By the method of the diluted Ising lattice the concentration dependences of temperatures of PT in these crystals are simulated.